Antibiotic prescribing patterns at outpatient clinics in Western and Coastal Kenya. - Melanie Kiener; Caroline Ichura; Bryson A Ndenga; Francis M Mutuku; Christabel A Winter; Victoria Okuta; Laura Mwambingu; Kevin Ogamba; Karren N Shaita; Charles Ronga; Philip Chebii; Jael Amugongo; et al. (PLOS Global Public Health)
Antimicrobial resistant pathogens are a leading cause of morbidity and mortality worldwide, with overuse and misuse of antimicrobials being key contributors. We aimed to identify factors associated with antibiotic prescriptions among patients presenting to clinics in Kenya. We performed a retrospective, descriptive cohort study of persons presenting to outpatient clinics in Western and Coastal Kenya, including symptoms, physical exams, clinician assessments, laboratory results and prescriptions. We reviewed 1,526 visits among 1,059 people who sought care from December 2019-February 2022. Median age was 16 (IQR 6-35) and 22% were under 5. 30% of malaria RDTs were positive and 3% of dengue RT-qPCRs were positive. Antibiotics were prescribed in 73% of encounters overall and in 84% among children under 5. In 48% of visits antibiotics were prescribed without a provisional bacterial diagnosis. In the multivariable model, factors associated with increased odds of an antibiotic prescription were the clinic in Western Kenya (OR 5.1, 95% CI 3.0-8.8), age less than or equal to 18 (OR 2.1, 95% CI 1.4-3.2), endorsement of cardiorespiratory symptoms (OR 5.2, 95% CI 3.2-8.3), a negative malaria RDT (OR 4.0, 95% CI 2.5-6.8), and a provisional diagnosis that could be bacterial in etiology (OR 5.9, 95% CI 3.5-10.3). High rates of antibiotic prescriptions are common even when associated diagnoses are not bacterial. Compared to our 2014-2017 cohort, we found higher rates of antibiotic prescriptions among children. Improved diagnostics to rule in alternative diagnoses as well as stewardship programs are needed.